Pattern of drug utilization and factors influencing long term blood sugar control among diabetics in a tertiary care hospital- an observational study - M. S., Raghu Prasada; Patil, Deepa; B. M., Vishwanath; A. S., Shankar; Patil, Umakant N.; Holyachi, Sharankumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To study the Pattern of drug prescribing, utilization, analyse effectives of different therapies and factors influencing medication failure and adherence to treatment among diabetics. Methods: The clinical study was conducted in JJM Medical College and Karuna Trust, Davangere, Karnataka. The patients with diabetes as diagnosed by consultant physician were observed for the pattern of blood glucose control. The fasting blood glucose of the patients were recorded at the end of 1st month, 6th month and 12th month of their treatment period. The study period was from June 2012 till August 2014. The study was conducted after institutional ethical clearance and informed consent was taken from all the patients. The pattern of drugs prescribed for the patients were also analysed. The pattern of control among patients with co morbidities were also analysed using paired sample t test. Results: The results showed that the prescribed drugs were able to control the blood glucose levels of the patients. The percentage of patients with FBS in controlled, mild to moderate control and uncontrolled group were 21%, 33.3% and 45.5% in early treatment period and 36%, 40.9%, and 22.7% after one year treatment period (Significant p value). The pattern of drug utilization showed that the most commonly used drugs were the combination of pioglitazone+glimipride+metformin (19%), combination of glibenclamide+ metformin (18%), only insulin (9%), combination of glimipride+metformin (8%) and combination of gliclazide+metformin (5%). Conclusions: The results show that the intervention by the consultant physician was successful in controlling the blood sugar levels and the reasons for failure of treatment and adherence to treatment were helpful for further treatment of patients. Further such studies in a larger sample will help the consultants in their treatment methods.